Safe Working environment with the Protect Labour Rights (Journal of Pedagogical Inventions and Practices, 2022)
The accomplishment of the 17 Sustainable Development Goals sanctioned by the UN General Assembly will depend on whether or not the goal 8, Decent works and economic development; goal 8.8,to promote safe working environment and protect labour rights . This paper discusses the meaning of Sustainable Development and how it is different from sustainability. Also, the paper discusses about the labour rights, safe working conditions and ways to promote it. The last section of the paper discusses about the two indicators of the goal 8.8 which are deadly and non deadly activity sacred and unsettled person. Both of which have huge implications on SDG’s goals. Without human resource no goal can be achieved, hence it is important to protect labour rights and provide safe working environment to all the mortal, admit the unsettled workers, in specially women migrants, and those in unstable occupation. Employees are drawn to a workplace that is devoid of injuries and accidents. Employees are more happy and productive when they work in a safe setting. For both companies and employees, safe working conditions are essential. Employees have a right to a safe working environment.